(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background: The goal of the accounting organizational structure of any department of the state is to reach the efficiency, effectiveness, harmony and time of work, quality of service, application of liability accounting based on the best choice, optimal use of working time and various resources, reducing expenses that have no value, and has been selected one of the formations of the Ministry of Higher Education and Scientific Research as the research community and the financial division of the research sample group for suffering from functional sagging, Waste, loss under traditional accounting practices. Materials and Methods: the goal of the research is to determine the digital value of errors and waste and waste of time and resources in the accounting work approved for the payroll unit based on the personal interview of individuals working in it individually and for the month of April 2021 and to present a proposed model to bribe these expenses. Results: lean accounting is a culture of censorship, measurement and administrative methods that reflect rational thinking, correct practices and best decisions through the use of its court tools, concept, correct, reliability of information and works to save time and money by eliminating losses in old systems. Conclusion: the most important findings of the research indicated that agile thinking and correct practices using the tools of securitization court work to reduce mistakes And provide resources (human, service, commodity, time) by eliminating the lost by taking advantage of the lost time of the record unit, which is characterized by efficiency and accounting knowledge and commissioning the work of organizing salaries to avoid accounting errors resulting from the application of traditional systems, in addition to the use of graceful accounting methods in the accounting cycle of units (salaries, records) helps to reduce expenses that do not add value to outputs while maintaining the quality of information.